Posttraumatic Perfusion Analysis of Quadriceps, Patellar, and Achilles Tendon Regeneration With Dynamic Contrast‐Enhanced Ultrasound and Dynamic Contrast‐Enhanced Magnetic Resonance Imaging: Preliminary Results. (12th August 2020) - Fischer, Christian; Miska, Matthias; Jung, Andreas; Weber, Marc‐André; Saure, Daniel; Schmidmaier, Gerhard; Weimer, Andreas; Moghaddam, Arash; Doll, Julian
Abstract : Objectives: The healing process of tendons after surgical treatment of tendon ruptures mainly depends on the perfusion of the tendon and its surrounding tissue. Dynamic contrast‐enhanced ultrasound (DCE‐US) and dynamic contrast‐enhanced MRI (DCE‐MRI) can provide additional information about the local microperfusion. In this pilot study, the feasibility of these techniques to assess the vascularization during tendon regeneration was evaluated. Methods: Between 2013 and 2015, 23 patients with surgical treatment of traumatic rupture of quadriceps, patellar, and Achilles tendons were involved. All patients received clinical follow‐up examinations at 6, 12, and at least 52 weeks postoperatively. Dynamic contrast‐enhanced US and DCE‐MRI examinations were performed 6 and 12 weeks postoperatively. Dynamic contrast‐enhanced US perfusion was quantified by the parameters peak enhancement, wash‐in area under the curve, rise time, and initial area under the curve. Correlations between these parameters were examined via the Spearman rank correlation. The clinical and functional outcomes were assessed via the Lysholm Knee Score and Knee and Osteoarthritis Outcome Score at 12 and 52 weeks postoperatively. Results: Fourteen patients with quadriceps (n = 8), patellar (n = 4) and Achilles (n = 2) tendon ruptures with complete follow‐up were available. The microperfusion could be successful assessed. We could detect a strong correlation of DCE‐US (peak enhancement) parameters with DCE‐MRI (initial area under the curve) parameters after 6 and 12 weeks. Conclusions: In this pilot study, DCE‐US was able to visualize the microperfusion of healing tendons with a strong correlation with DCE‐MRI. Our initial results are in favor of DCE‐US as a potential quantitative imaging tool for evaluating the vascularization in tendon regeneration as a complementary method.